Sustainable urban pavement for cities affected by El Niño using porous concrete - Aguirre, B. (2021)
The El Niño phenomenon is caused by the change in atmospheric pressures, which produce the accumulation of hot surface waters on the eastern flank of the Pacific Ocean; causing intense rainfall that runs over the surface affecting the urban drainage of the city due to the lack of a permeable pavement; porous concrete allows infiltration of surface water runoff through its pores. The present investigation evaluates porous concrete in the range of w/c relationships of 0.30 and 0.32; the results indicate that the compressive strength, flexural strength and permeability coefficient increase; and that the surface runoff, cost, water footprint and carbon footprint are lower than conventional concrete.